Catching-up and inflation in Europe: Balassa-Samuelson, Engel's law and other Culprits - Balázs Égert (Center for Economic Studies and ifo Institute (CESifo), 2010)
This study analyses the impact of economic catching-up on annual inflation rates in the European Union with a special focus on the new member countries of Central and Eastern Europe. Using an array of estimation methods, we show that the Balassa-Samuelson effect is not an important driver of inflation rates. By contrast, we find that the initial price level and regulated prices strongly affect inflation outcomes in a nonlinear manner and that the extension of Engel's Law may hold during periods of very fast growth. We interpret these results as a sign that price level convergence comes from goods, market and non-market service prices. Furthermore, we find that the Phillips curve flattens with a decline in the inflation rate, that inflation is more persistant and that commodity prices have a stronger effect on inflation in a higher inflation environment.
Keywords: E43; E50; E52; C22; G21; O52; 330; European Union; inflation; Balassa-Samuelson; real convergence; catching up; Bayesian model average; non-linearity; Inflationsrate; Inflationskonvergenz; Entwicklungskonvergenz; Balassa-Samuelson Effekt; Mikroökonomische Konsumfunktion; Phillips-Kurve; Schätzung; EU-Staaten (Osteuropa); EU-Staaten